Bootstrap estimation of willingness to pay in contingent valuation models: Analysis of the scenario of balanced binary responses - Ledesma Goyzueta, Luis (2017)
This research aims to show the application of the bootstrap method in the process of estimating the willingness to pay (WTP) for a determined environmental service, using the binary choice model for contingent valuation. The main contribution of the research, is the inclusion of an additional criterion in the bootstrap process, in which samples are randomly selected containing balanced values in the dependent dichotomous variable. For illustrative purposes, it is used the data base from the Postigo (2011) study, in order to estimate the mean, standard error and the confidence interval of the WTP through de bootstrap method. In comparison of the results obtained in the baseline scenario, if the bootstrap method with balanced subsamples is applied, it would be obtained logit coefficients with greater statistical significance and also lower mean and standard error of the WTP.